SAT0043 Il-33/st2-mediated inflammation in endothelial cell is directly aggravated by il-6 during lupus nephritis - Yu, S.L.; Huo, Y.B.; Huang, C.H.; Tao, Y.; Huang, W.H.; Wong, C.K.; Tam, L.S.; Qiu, H.N.; Chen, R.L.; Zhong, L. (Annals of the rheumatic diseases, 2018)
Background”Alarmins” are prototypic endogenous pro-inflammatory factors as they are released from necotic cells and provoke local damage or systemic inflammation. Evidences are accumulating to support the inclusion of ”Alarmins” as targets of autoreactivity as well as inducers in the pathogenesis of Systemic Lupus Erythematosus (SLE). Interleukin (IL)−33 is a novel member of the family of ”Alarmins” because of its characteristics and functions in mediating host immune responses. On this background, we sought to determine the role of IL-33/ST2 axis in lupus pathogenesis. The role of IL-33/ST2 axis has not previously been described in lupus nephritis.ObjectivesThis project will study the followings:1 To determine whether IL-33 was present in renal glomerular endothelial cells;2 To assess the functional and intracellular signal transuction mechanisms regulating the link between IL-33/ST2-mediated innate immunity and inflammation in human umbilical vein endothelial cells (HUVECs).ResultsThis study, for the first time, showed that IL-33 was pathologically expressed in the kidney tissue of patients with lupus nephritis and not in that of subjects with relative normal renal tissues from atrophy. However, no significant difference was observed between patients with lupus nephritis and kidney cancer. Immunofluorescence (IF) for IL-33 in kidney was performed in lupus patients. IL-33 was clearly seen in glomeruli and also in peritubular areas. To determine whether the IL-33 staining in glomeruli area was in endothelium, multiple staining for IL-33, CD34 (a marker for endothelial cells) and 4’,6-diamidino-2-phenylindole (DAPI) stained for cell nuclei was performed. Co-localization of IL-33 and DAPI in CD34 positive cells demonstrates IL-33 staining in the nucleus of glomerular endothelial cell of lupus kidney. Expression of intracellular but not surface ST2 was increased in plasmacytoid dendritic cells/pDC (CD16-CD14-CD85k+CD123+) of lupus patients when compared with healthy controls. Incubation of HUVECs with IL-33 and/or IL-12 increased the production of IL-6, but IL-4, IL-5, IL-6, IL-13 and TNF-αwas not produced.ConclusionsAs a result of external stimuli or infection, renal glomerular endothelial cells undergo cellular death and release the ”Alarmin”, IL-33, to alert the lupus immune system. Released IL-33 interact with their target cells, pDC via their specific receptor ST2 to subsequently induce innate and adaptive responses, activate inflammatory pathways in the pathogenesis of lupus nephritis.AcknowledgementsThis work was supported by National Science Foundation of China (81300585), Science and Technology Planning Project of Guangdong Province (2014A020212322) and Natural Science Foundation of Guangdong Province (2015A030313477).Disclosure of InterestNone declared